1996
DOI: 10.3109/08860229609047717
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Hypothalamic-Pituitary Axis in Uremic Males Using Dynamic Tests. The Possible Role of Testicular Inhibin: A Preliminary Report

Abstract: Two dynamic tests (Gn-RH i.v. and clomiphene citrate-CC p.o.) were used to evaluate the hypothalamic-pituitary axis in hemodialysis patients and renal transplant recipients (recipients). In the Gn-RH test the gonadotropin secretion was maximally decelerated in hemodialysis patients while it was normal in recipients. During the CC test a decrease of gonadotropin secretion, chronically and quantitatively identical for both group, was found; while on the following test days an increase was noted, which was more a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 38 publications
0
9
1
Order By: Relevance
“…The present study showed that males with chronic renal failure on hemodialysis have hyperestrogenemia. It is not clear why our results differ from those of Mastrogiacomo et al (1988), Kokot et al (1995), and Chryssicopoulos et al (1996). However, these studies can be faulted for the use of inappropriate controls and lack of morning blood samples.…”
Section: Journal Of Andrology · March/april 2000 Andr 21_207 Mp_260contrasting
confidence: 65%
See 2 more Smart Citations
“…The present study showed that males with chronic renal failure on hemodialysis have hyperestrogenemia. It is not clear why our results differ from those of Mastrogiacomo et al (1988), Kokot et al (1995), and Chryssicopoulos et al (1996). However, these studies can be faulted for the use of inappropriate controls and lack of morning blood samples.…”
Section: Journal Of Andrology · March/april 2000 Andr 21_207 Mp_260contrasting
confidence: 65%
“…The endocrinologic status of chronic renal failure in males with elevated gonadotropin levels and decreased testosterone levels is well documented (Handelsman, 1985;Mastrogiacomo et al, 1988;Handelsman and Dong, 1993). In contrast, the findings relating to estrogen levels have been variable: increased (Lim and Fang, 1976), decreased (Mastrogiacomo et al, 1988;Kokot et al, 1995) or unchanged (Chryssicopoulos et al, 1996). The present study showed that males with chronic renal failure on hemodialysis have hyperestrogenemia.…”
Section: Journal Of Andrology · March/april 2000 Andr 21_207 Mp_260mentioning
confidence: 47%
See 1 more Smart Citation
“…FSH concentration appears to increase in uraemic patients because of the damage to sertoli cells, resulting in the suppression of inhibin production (Chryssicopoulos et al, 1996). FSH concentration appears to increase in uraemic patients because of the damage to sertoli cells, resulting in the suppression of inhibin production (Chryssicopoulos et al, 1996).…”
Section: Studies Of Men With Esrd Have Shown a Wide Variability Regard-mentioning
confidence: 99%
“…Inhibin, produced by Sertoli cells, negatively regulates FSH release from the pituitary gland. FSH concentration appears to increase in uraemic patients because of the damage to sertoli cells, resulting in the suppression of inhibin production (Chryssicopoulos et al, 1996).…”
Section: Studies Of Men With Esrd Have Shown a Wide Variability Regard-mentioning
confidence: 99%